Kewenangan Pemerintah Daerah dalam Pemenuhan Hak atas Bantuan Hukum Bagi Masyarakat Miskin dan Kelompok Rentan - Petrus Antonius Ayub Adha (Journal of Contemporary Law Studies, 2026)
This article examines the authority of local governments in fulfilling the right to legal aid for the poor and vulnerable groups within the framework of the rule of law, human rights, and regional autonomy. Legal aid constitutes a fundamental component of access to justice and is constitutionally grounded in the obligation of the state to guarantee equality before the law. Although Law Number 16 of 2011 on Legal Aid provides a statutory basis for local government involvement, ambiguities remain regarding whether such authority is mandatory or discretionary. This study employs normative legal research using statutory, conceptual, and normative case approaches to analyze the constitutional and juridical foundations of local government authority. The findings demonstrate that the authority of local governments in providing legal aid is not merely a policy option, but a binding legal obligation derived from constitutional principles and human rights guarantees. Interpreting legal aid as discretionary would contradict the essence of the rule of law and the protection of fundamental rights. Therefore, local governments are required to institutionalize and finance legal aid through adequate regulation and budgeting to ensure substantive access to justice.